Acoustic scattering characteristics and inversions for suspended concentration and particle size above mixed sand and mud beds. (1st February 2021) - Thorne, Peter D.; Lichtman, Ian D.; Hurther, David
Abstract: The majority of reported field studies, using acoustic backscattering, for the measurement of nearbed suspended sediment processes, have been focussed on field sites with sand size fractions and unimodal size distributions. However, in many sedimentary environments, and particularly for estuaries and rivers, sands and muds coexist in the bed sediment substrate, forming a size regime that is often bimodal in nature. To examine the interaction of sound in these more complex sedimentary environments a numerical study is presented based on observations of sediment size distributions measured in the Dee estuary, UK. The work explores the interpretation of the backscatter signal from a mixed sediment composition in suspension, with mud-sand fractions varying with height above the bed. Consideration is given to the acoustical scattering properties and the inversion of the backscatter signal to extract information on the suspension. In common with most field deployments, the scenarios presented here use local bed sediments for the acoustic inversion of the backscattered signal. The results indicate that in general it is expected that particle size and concentration will diverge from what is actually in suspension, with the former being overestimated and the latter underestimated. Highlights: A numerical study explores acoustic backscatter from a suspension of a mud-sand mixture varying with height above the bed. Changing mud-sand composition above the bed may lead to errors in the acoustic estimates of particle size and concentration. Using bed samples, for acoustic inversions can leadto overestimates of suspended size and underestimates of concentration.